2013
DOI: 10.1095/biolreprod.113.111245
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Exposure Alters Pebp1 DNA Methylation and Protein Profile Involved in MAPK Signaling Pathway in Mice Testis1

Abstract: Many studies have addressed the role of cigarette smoking on semen quality, but the exact mechanisms remain inconclusive. To evaluate the detrimental effects of smoking on the spermatogenesis process, we initially screened and investigated 31 differentially expressed proteins extracted from the testes of mice exposed daily to cigarette smoke using matrix-assisted laser desorption/ionization-time of flight-mass spectrometry analysis. Data mining analysis showed that these 31 proteins were categorized into five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…PEBP1 is an essential protein involved in spermatogenesis through its interaction with ERKs. Mice exposed to cigarette smoke were shown to have elevated methylation level near Pebp1 transcriptional start site, which has been suggested to decrease Pebp1 expression and in turn cause the inactivation of ERK pathway resulting in spermatogenetic defects (Xu et al, ). Apart from hypermethylation, smoking may also promote DNA hypomethylation.…”
Section: Cigarette Smoking and Epigenetic Alterationsmentioning
confidence: 99%
“…PEBP1 is an essential protein involved in spermatogenesis through its interaction with ERKs. Mice exposed to cigarette smoke were shown to have elevated methylation level near Pebp1 transcriptional start site, which has been suggested to decrease Pebp1 expression and in turn cause the inactivation of ERK pathway resulting in spermatogenetic defects (Xu et al, ). Apart from hypermethylation, smoking may also promote DNA hypomethylation.…”
Section: Cigarette Smoking and Epigenetic Alterationsmentioning
confidence: 99%
“…However, the role of paternal smoking in DNA methylation in offspring is less understood. Xu et al, found significant differences in gen-specific methylation in sperm DNA of mice exposed to cigarette smoke [112]. However, in humans paternal smoking was not found to be linked to altered H19 or IGF2 DMR methylation in umbilical cord DNA of newborns [113].…”
Section: Smokingmentioning
confidence: 98%
“…52 This indicates that PEBP1 function is essential for normal development of sperm. Recent studies on cigarette smoking showed that the protein profile in the cells could be altered during spermiogenesis.…”
Section: Pebp1 In Spermiogenesismentioning
confidence: 99%
“…Spermiogenesis in mice was altered as a result of cigarette smoking, as the CpG sites in PEBP1 transcription sites were methylated excessively, thereby altering the pathways important for the normal sperm development in mice. 52 This indicates that PEBP1 function is essential for normal development of sperm. 53…”
Section: Pebp1 In Spermiogenesismentioning
confidence: 99%